(untitled) (CAHIERS MAGELLANES-NS, 2024)
An unsuccessful attempt of a fertilized egg or embryo to deposit itself in the uterine endometrial layer is known as implantation failure, resulting in an unsuccessful pregnancy. Recurring implantation failure (RIF) describes the inability to implant high-quality embryos more than once. Embryo chromosomal defects, endometrial disorders, and immune system concerns are among the many possible causes. The purpose of this study was to investigate the function of the endometrial expression of leukaemia inhibitory factor (LIF), glycoprotein 130 (gp130) receptor, IL-1β, and HB-EGF molecules in patients of primary unexplained infertility, as well as the release of these molecules throughout the window of implantation. The study was conducted on 70 women diagnosed with primary unexplained infertility for at least two years and repeated implantation failures following IVF-ET, along with 50 normal fertile women who participated as a control group. Tissue from the endometrium and uterine flushing were collected. The expression of LIF, gp130 IL-1β, and HB-EGF mRNA was tested by RNA extraction and PCR. The control group were significantly higher than those in the patient group (p<0.05) concerning LIF, gp130 IL-1β. In conclusion, Endometrial LIF, gp130 IL-1β mRNA expression may serve as a molecular indicator of infertility with no known cause.